1996
DOI: 10.1152/ajplung.1996.271.5.l726
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and its alpha 5 beta 1-integrin receptor are involved in the wound-repair process of airway epithelium

Abstract: The cell migration that occurs during wound repair is dependent on modifications of the cell-matrix interaction in which extracellular matrix proteins and their receptors, the integrins, are involved. To study the interactions between airway epithelial cells and the extracellular matrix during the process of wound repair, we developed an in vitro wound model of human epithelial cells. Surface epithelial cells were dissociated from human nasal polyps and cultured on a type I collagen matrix. At confluency, a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 0 publications
4
86
0
1
Order By: Relevance
“…One of the early responses to airway injury is the migration of the remaining epithelial cells over a fibronectin-containing provisional matrix (5). Previous in vitro studies have demonstrated that fibronectin promotes the migration of airway epithelial cells (13). In the present study, we have extended these observations by demonstrating that airway epithelial cell migration requires the formation of fibronectin matrix fibrils.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…One of the early responses to airway injury is the migration of the remaining epithelial cells over a fibronectin-containing provisional matrix (5). Previous in vitro studies have demonstrated that fibronectin promotes the migration of airway epithelial cells (13). In the present study, we have extended these observations by demonstrating that airway epithelial cell migration requires the formation of fibronectin matrix fibrils.…”
Section: Discussionsupporting
confidence: 64%
“…Migrating airway epithelial cells continuously secrete and polymerize fibronectin into insoluble ECM fibrils (13). In an initial step of fibronectin matrix formation, cells bind the NH 2 -terminal region of fibronectin in a specific and saturable manner (22).…”
Section: Fibronectin Induces a Biphasic Effect On Cell Migrationmentioning
confidence: 99%
“…During the repair process after airway epithelial injury, cells actively synthesise a5-integrin at the leading edge of cells [19,20] and require a functional cooperation of integrins with MMP-14 for cell migration [17]. These proteins are PC substrates and activated MMP-14 can facilitate the maturation of pro-MMP-2 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since the upregulation of MMPs, a5-integrin and the ECM proteins collagen and fibronectin are common features of EMT [17][18][19][20], we assessed the expression levels of these genes in mock and PC1/3 cells using realtime PCR. Figure 5a shows that PC1/3 overexpression resulted in markedly enhanced expression of MMP-2, MMP-3, and a5-integrin in NCI-H292 cells, while the expression levels of MMP-1, -7, -9 and -10 were not changed; increased MMP-2 expression was confirmed by Western blotting and zymography ( fig.…”
Section: Pc1/3 Overexpression Enhances Expression Of Emt Markers Mmpmentioning
confidence: 99%
“…Apical expression of ␤ 1 integrins has been observed on epithelial cells during inflammation, wound healing and ischaemia. [15][16][17] Endothelial cells also express apical ␤ 1 integrins, which are involved in interactions with leukocytes when activated during the process of inflammation. 18 In conclusion, ␤ 1 integrins are available to external ligands, especially during clinically relevant conditions.…”
Section: Introductionmentioning
confidence: 99%